Religious education and teaching young people about humanity: Suggesting a new role for RE and for the academic study of religions in Sweden - Svensson, Jonas (Temenos, 2015)
This article is a suggestion for the rethinking of the role and purpose of religious education (RE) in Swedish public schools, in relation to two major recent reforms: of teachers training (2012) and of syllabi for RE (2011). Based on a notion of the ‘humanistic’ study of religions as he study of religion as a human cultural product, the article argues that a RE - mainly in lower and upper secondary school - informed by contemporary theoretical development, better than any other school subject can cater for the important task of educating young people about who they, as human beings, are and why. To substantiate this claim, the content of the above mentioned reforms are presented, and placed in historical context. Furthermore, the article provides a set of examples of how actual teaching may be structured to fulfil its proposed new task, with a basis in the current syllabi for lower and upper secondary school.